2011
DOI: 10.3892/ijo.2011.1178
|View full text |Cite
|
Sign up to set email alerts
|

State of heat shock factor 1 expression as a putative diagnostic marker for oral squamous cell carcinoma

Abstract: Abstract. Heat shock factor 1 (HSF1) is responsible for expression of a large class of heat shock proteins that have been implicated in the malignant phenotype of human cancers. Little is known about the effect of a high level of HSF1 on the behavior of oral squamous cell carcinoma (OSCC). In this study, we assessed the value of HSF1 for predicting clinical outcomes in OSCC. Quantitative reverse transcriptase-polymerase chain reaction and Western blotting showed that the expressions of HSF1 mRNA and protein in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 36 publications
3
24
0
Order By: Relevance
“…High levels of HSF1 and HSPs expression were observed in a broad range of human tumors [ 27 - 30 ]. Moreover, it has been shown that increased HSF1 expression is associated with reduced survival of cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of HSF1 and HSPs expression were observed in a broad range of human tumors [ 27 - 30 ]. Moreover, it has been shown that increased HSF1 expression is associated with reduced survival of cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated nuclear HSF1 expression has also been observed in cervical cancer, colon cancer, lung cancer, pancreatic cancer, prostate cancer, and meningioma [23]. In addition, nuclear HSF1 expression is associated with tumor size in OSCC [95], and with metastasis and poor survival in endometrial cancer [96]. Further characterization of HSF1 activation in cancer was performed using high-throughput ChIP-seq technologies that profiled targeted genes of HSF1 in a broad range of human cancer cell lines and specimens [23].…”
Section: Targeting Fragile Proteostasis In Cancer: Therapeutic Stratementioning
confidence: 99%
“…Elevated expression of HSF1 has been associated with advanced stages in breast cancer, hepatocellular carcinoma and oral squamous cell carcinoma, suggesting a broad role for the factor these processes [21, 5254]. It seems likely that the ability of HSF1 to promote cancer cell signaling, to enhance polyploidy and evade cell inactivation pathways likely contribute to tumor progression as well as initiation.…”
Section: Introductionmentioning
confidence: 99%